2014
DOI: 10.1108/cg-10-2011-0076
|View full text |Cite
|
Sign up to set email alerts
|

Managerial role in organizational CSR: empirical lessons from Ghana

Abstract: Purpose – The purpose of this paper is to examine the managerial role in the practices of corporate social responsibility (CSR) in developing economies. Design/methodology/approach – The paper takes the form of an empirical analysis of employees' opinions based on a quantitative survey of 100 middle and senior level managers from four organisations chosen from relatively high impact industry sectors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 58 publications
(72 reference statements)
0
30
0
Order By: Relevance
“…Notwithstanding, some SMEs confront this negative institutional limitations to find innovative ways of addressing consumer needs, where such are inadvertently or deliberately constrained by poor regulations and ineffective policy enforcement (Hamann et al, in press The foregoing assertion is another example of CSR practices by SMEs playing a supplementary role in the marketplace. Another key issue that has been highlighted in other studies on CSR in developing countries is corruption -especially as a marketplace phenomenon (e.g., Abugre, 2014). All the participants in Nigeria and Tanzania recognise that corruption is an issue; however, not all admit that it is a problem for their own business.…”
Section: Csr In the Marketplacementioning
confidence: 99%
“…Notwithstanding, some SMEs confront this negative institutional limitations to find innovative ways of addressing consumer needs, where such are inadvertently or deliberately constrained by poor regulations and ineffective policy enforcement (Hamann et al, in press The foregoing assertion is another example of CSR practices by SMEs playing a supplementary role in the marketplace. Another key issue that has been highlighted in other studies on CSR in developing countries is corruption -especially as a marketplace phenomenon (e.g., Abugre, 2014). All the participants in Nigeria and Tanzania recognise that corruption is an issue; however, not all admit that it is a problem for their own business.…”
Section: Csr In the Marketplacementioning
confidence: 99%
“…Although there is evidence of CSR taking place in Ghana as far back as 1939 (Ofori 2010a(Ofori , 2010b, scholarship in the area is a recent phenomenon (Ofori 2007a(Ofori , 2007bAbugre 2014). It is therefore not surprising that much of the included literature is post 2010.…”
Section: Publication Activitiesmentioning
confidence: 99%
“…2016); seven articles constituting 14.89% (e.g. Abugre, 2014;Puplampu and Dashwood, 2011) related to organisation and management studies, emphasising managerial roles in CSR and other institutional characteristics that serve as predictors of CSR, while five papers (10.64%) were categorised as conceptual/literature review (e.g. Amponsah-Tawiah & Dartey-Baah, 2012;Hinson et.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…According to the study, the companies predominantly aligned their CSR to the Millennium Development Goals (replaced by the Sustainable Development Goals in 2016), specifically focusing on issues such as health, education and community development initiatives. Conversely, a quantitative survey by Abugre (2014) found that managements' commitment in organisational CSR positively affects the implementation of responsibility policies and practices. Insights from the study suggest that CSR challenges mostly stem from lack of management's commitment to CSR initiatives particularly in allocating resources to such activities.…”
Section: Multi-sectorsmentioning
confidence: 95%